ANALISA PENGGUNAAN SAND SCREEN PADA POMPA SUCKER ROD PUMP DALAM MENGATASI PROBLEM KEPASIRAN DI SUMUR "T" LAPANGAN KALREZ PETROLEUM (SERAM) LIMITED - Tasya Ivany Solissa; Tun Sriana; Valentyn B Hattu (Journal Mechanical Engineering, 2025)
In producing oil, production problems often occur, one of which is the problem of sand. The sand problem occurs when the production flow rate exceeds the maximum limit of the specified critical flow rate, due to fluid friction forces and a decrease in pore pressure in the formation and cementation in the rock. This can cause production losses in wells, due to decreased production rates and damage to production equipment. At Kalrez Petroleum (Seram) Ltd "T" wells, sand problems are often found in the sucker rod pump. To overcome this problem, the Kalrez Petroleum (Seram) Ltd Well "T" used a mechanical method, namely, installing a sand screen on the sucker rod pump. By using a sand screen, it is hoped that it can overcome the sand problem in the Kalrez Petroleum (Seram) Ltd "T" Well so that the production well can work smoothly and produce oil of good quality and economically. The results of the sand screen size analysis show that the correct size is 0.012 inch. The results of further analysis showed an increase in fluid production rate from 3.9 bbl/day to 5.8 bbl/day after using the sand screen. The results of the economic analysis show that the use of a sand screen on the sucker rod pump (SRP) in the 'T' well is feasible because it has economic value with the oil price obtained at 50 US$ / bbl, the NPV is 16,913 USD, and the project success (IRR) reaches 56%, and a payout time of 1 year. Keywords: Sucker Rod Pump, Sand Problems, Sand Screen, Flow Rate, Economics